Percept of the duration of a vibrotactile stimulus is altered by changing its amplitude - Francisco, Eric M.; Holden, Jameson K.; Nguyen, Richard H.; Favorov, Oleg V.; Tommerdahl, Mark (Frontiers in Systems Neuroscience, 2015)
There have been numerous studies conducted on time perception. However, very few of these have involved tactile stimuli to assess a subject’s capacity for duration discrimination. Previous optical imaging studies in non-human primates demonstrated that increasing the duration of a vibrotactile stimulus resulted in a consistently longer and more well defined evoked SI cortical response. Additionally, and perhaps more interestingly, increasing the amplitude of a vibrotactile stimulus not only evoked a larger magnitude optical intrinsic signal, but the return to baseline of the evoked response was much longer in duration for larger amplitude stimuli. The authors hypothesized that the magnitude of a vibrotactile stimulus could influence the perception of its duration. In order to test this hypothesis, subjects were asked to compare two sets of vibrotactile stimuli. When vibrotactile stimuli differed only in duration, subjects typically had a difference limen (DL) of approximately 13%, and this followed Weber’s Law for standards between 500 and 1500 ms, as increasing the value of the standard yielded a proportional increase in DL. However, the percept of duration was impacted by variations in amplitude of the vibrotactile stimuli. Specifically, increasing the amplitude of the standard stimulus had the effect of increasing the DL, while increasing the amplitude of the test stimulus had the effect of decreasing the DL. A pilot study, conducted on individuals who were concussed, found that increasing the amplitude of the standard did not have an impact on the DL of this group of individuals. Since this effect did not parallel what was predicted from the optical imaging findings in somatosensory cortex of non-human primates, the authors suggest that this particular measure or observation could be sensitive to neuroinflammation and that neuron-glial interactions, impacted by concussion, could have the effect of ignoring, or not integrating, the increased amplitude.